2020
DOI: 10.3390/nu12113569
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Habits and Mediterranean Diet Adherence on Sleep Quality during Pregnancy. The GESTAFIT Project

Abstract: We examined the association of the dietary habits and the Mediterranean diet (MD) adherence with sleep quality during pregnancy. A food frequency questionnaire and the Mediterranean Food Pattern were employed to assess dietary habits and MD adherence, respectively. Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI) global score (n = 150; mean age 32.9 ± 4.6 years). A higher consumption of fruits was associated with better sleep quality at the 16th gestational week (g.w.; p < 0.05). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…As for the country of origin, 57.14% ( n = 8) ( 18 – 20 , 28 – 32 ) of the articles were carried out in Spain, two studies were carried out in the Netherlands (14.29%) ( 33 , 34 ), one in England (7.14%) ( 35 ), one in France (more specifically on the island of Guadeloupe) (7.14%) ( 36 ), one in the United States (7.14%) ( 37 ), and, finally, one that included participants from the United States, Greece, and Crete (7.14%) ( 21 ). In terms of design, of the 14 studies included, five were cohorts (35.71%) ( 21 , 33 , 34 , 36 , 37 ), four clinical trials (28.57%) ( 18 , 29 , 31 , 35 ), three cases and controls (21.43%) ( 24 , 30 , 32 ), and two were cross-sectional studies (14.29%) ( 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As for the country of origin, 57.14% ( n = 8) ( 18 – 20 , 28 – 32 ) of the articles were carried out in Spain, two studies were carried out in the Netherlands (14.29%) ( 33 , 34 ), one in England (7.14%) ( 35 ), one in France (more specifically on the island of Guadeloupe) (7.14%) ( 36 ), one in the United States (7.14%) ( 37 ), and, finally, one that included participants from the United States, Greece, and Crete (7.14%) ( 21 ). In terms of design, of the 14 studies included, five were cohorts (35.71%) ( 21 , 33 , 34 , 36 , 37 ), four clinical trials (28.57%) ( 18 , 29 , 31 , 35 ), three cases and controls (21.43%) ( 24 , 30 , 32 ), and two were cross-sectional studies (14.29%) ( 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, adherence to the Mediterranean diet was measured through the MEDAS (Mediterranean Diet Adherence Screener) in 3 studies ( 18 , 29 , 31 ), through a FFQ (Food frequency questionnarire) in 7 studies ( 19 , 20 , 31 35 ), one study through the Mediterranean diet score (MDS) ( 21 ), another study through the index created by Trichopoulou ( 28 ) and another study with the aMED (alternative Mediterranean diet) ( 37 ). In addition there was a study that evaluated the Mediterranean diet with three indices, the MEDAS, the one created by Trichopoulou and the one created by Panagiotakos ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A laboratory study explored the hypothesis that the content in anthocyanins of isogenic wheat lines may be determinant to exert positive effects on neurodegenerative disorders [25]. Concerning sleep quality, two studies have shown an association of higher adherence to the Mediterranean diet during pregnancy [26] and food security with sleep quality [27], respectively; a third study from our group provided the first evidence of a potential role played by dietary polyphenol content in sleep quality [28]. Diet quality has also been related to depression in two studies: Cebrino et al [29] reported that non-depressive individuals had a higher diet quality than depressive ones in a nationwide cross-sectional study conducted in Spain; in the study of Marozoff et al [30], the authors showed that increasing Healthy Eating Index-Canada scores were associated with fewer physician visits for depression in a prospective investigation of adults living in Alberta (Canada).…”
mentioning
confidence: 99%